THE EFFECTS OF DISCOVERY LEARNING IN THE STUDY RESULTS FOR THE ELEVENTH GRADE STUDENTS MAJORING IN LIGHT VEHICHLE ENGINEERING ON THE COMPREHENSION OF STEERING WHEEL IN SMKN 1 PALANGKA RAYA ACADEMIC YEAR 2017/2018 - Kristian Adi Candra; Debora (Jurusan Pendidikan Teknologi Dan Kejuruan, 2019)
Guided discovery (discovery learning) is a learning model developed based on constructivism. This model emphasizes the importance of understanding structure or important ideas towards a discipline, through active student involvement in the learning process. Students learn through active involvement and the teacher encourages students to gain experience by carrying out activities that enable them to find principles for themselves. The purpose of this study was to find out the effect of the Model on Student Learning students’ results in material Understanding the Light, elevents grade students Steering System for Light Vehicle Engineering in SMK 1 Palangka Raya Academic Year 2017/2018. This research is a kind of pre-experiment research with the method of one group pretest-posttest design carried out at SMK Negeri 1 Palangka Raya. The sample from this study was a class XI student of Light Vehicle Engineering, amounting to 32 people. The research data is quantitative data from learning outcomes test instruments in the form of pretest scores and posttest scores. before use, the instrument was tested in class XI Light Vehicle Engineering at SMK Negeri 1 Katingan Hilir. The results of the instrument trials from 40 multiple choice questions obtained 25 items accepted to be used as instruments in this study. The results of the parametric hypothesis test using the t-test two correlated samples obtained tcount> t table (15.3> 2.03). Because tcount = 15.3 is greater than t table = 2.03, then this means that H0 is rejected and H1 is accepted, which indicates that there is an influence on student learning outcomes taught using Discovery Learning models in Steering System subject matter in Class XI Light Vehicle Engineering at SMK Negeri 1 Palangka Raya Academic Year 2017/2018. So it can be concluded that student learning outcomes after learning with Discovery Learning models are better than student learning outcomes before being learned by Discovery Learning models in subject matter Understanding The Steering system in SMK Negeri 1 Palangka Raya.